Effect of the rider position during rising trot on the horse´s biomechanics (back and trunk kinematics and pressure under the saddle) - Martin, P.; Cheze, L.; Pourcelot, P.; Desquilbet, L.; Duray, L.; Chateau, H. (Journal of Biomechanics, 2016)
Knowledge about the horse-saddle-rider interaction remains limited. The aim of this study was to compare the effect of the rider?s position at rising trot on the pressure distribution, spine movements, stirrups forces and locomotion of the horse. The horse?s back movements were measured using IMUs fixed at the levels of thoracic (T6, T12, T16) and lumbar (L2, L5) vertebrae, the pressure distribution using a pressure mat and stirrups forces using force sensors. The horse´s and rider´s approximated centres of mass (COM) were calculated using 2D reflective markers. To compare both trot phases (rider seated/rider standing), three horses were trotted at the rising trot by the same rider. Means±SD of each parameter for sitting and standing were compared using a Student´s t test (p=0.05). Stirrups forces showed two peaks of equal magnitude in every stride cycle for left and right stirrups but increased during the standing phase. Simultaneously, the pressure for the whole mat significantly increased by +3.1 kPa during the sitting phase with respect to standing phase. The T12-T16 and T16-L2 angular ranges of motion (ROM) were significantly reduced (-3.2° -1.2°) and the T6-T12 and L2-L5 ROM were significantly increased (+1.7° +0.7°) during sitting phase compared to standing phase. During rising trot, the sitting phase does not only increase the pressure on the horse?s back but also reduces the back motion under the saddle compared to the standing phase. These results give new insights into the understanding of horse-rider interactions and equine back pain management.